The Challenge of Territorial Systemic Analysis for Peacebuilding in Colombia - Cruz Maldonado, Jury Natalia (Análisis Jurídico - Político, 2025)
This article reflects on the need to structure a systemic analysis of Colombian rural territory as a crucial challenge in the context of implementing public land policies and peacebuilding in Colombia. It examines the conditions for configuring a scenario that articulates the action of institutions and democratic participation in land management, from the perspectives of scientific and technological innovation, based on the following guiding questions: What are the challenges facing the government and civil society in addressing the issue of access to and use of rural land in the process of just and responsible land governance? What is the functionality of three conjuncture public policies for achieving territorial peace: Multipurpose Cadastre, Social Ordering of Rural Property, and the Land Administration System? The analysis uses a qualitative and descriptive approach. It interprets, on the one hand, the experience of professionals specialized in land administration, who provide an account of the use of geospatial technologies in this field, through in-depth interviews. On the other hand, it reviews the evolution of the legal-normative framework and the documentary analysis. The results describe the analytical value that a geospatial ecosystem represents for the contemporary country. This revolutionary tool is crucial for comprehensive knowledge of the territory, which requires effective, participatory, and equitable intervention to strengthen the institutions that manage land and peace towards sustainable development